Thermogravimetric Analysis of Lignins - T. Kosankar, Prakash; Ingle, V.N.; Pokale, W.K. (Asian Journal of Chemistry, 2010)
Thermogravimetric analysis of lignins isolated from Ailanthus excelsa, Cassia siamea, Delonix regia, Moringa oleifera and Vltex negundo have been carried out. An attempt has also been made to determine other thermodynamic parameters like activation energy (Ea) and enthalpy of activation (ΔH) by using Sharp-Wentworth method. The data obtained confirmed the validity of Arrhenius equation.